Rapid Aspirin Desensitization is Safe and Feasible in Patients With Stable and Unstable Coronary Artery Disease: A Single-Center Experience. (July 2019) - Jackson, Matthew; Callaghan, Sarah; Stapleton, John; Bolton, Sarah; Austin, David; Muir, Douglas F.; Sutton, Andrew G. C.; Wright, Robert A.; Williams, Paul D.; Hall, Jim A.; Carter, Justin; de Belder, Mark A.; et al.
Aims: There are limited data on aspirin (ASA) desensitization for patients with coronary disease. We present our experience with a rapid nurse-led oral desensitization regimen in patients with aspirin sensitivity undergoing coronary angiography. Methods: This single-center retrospective observational study includes patients with a history of ASA sensitivity undergoing coronary angiography with intent to perform percutaneous coronary intervention (PCI). Results: Between January 2012 and January 2017, 24 patients undergoing coronary angiography for stable coronary disease (7 cases) or acute coronary syndromes (non-ST-segment myocardial infarction [NSTEMI; 8 cases], STEMI [9 cases]) underwent aspirin desensitization having reported previous reactions to aspirin. At initial presentation, previous sensitivity reactions were reported as: mucocutaneous reactions in 17 patients (urticaria in 3 [13%], nonurticarial rash in 6 [25%], angio-oedema in 8 [33%]), respiratory sensitivity in 4 (17%), and systemic anaphylactoid reactions in 3 (13%). Seventeen (71%) patients underwent PCI. Desensitization was acutely successful in 22 (92%) patients and unsuccessful in 2 (8%) patients who both had a single short-lived episode of acute bronchospasm treated successfully with nebulized salbutamol. Fifteen successfully desensitized patients completed 12 months of aspirin; no patient had recurrent hypersensitivity reaction. Aspirin was stopped prior to 12 months in 7 patients (replaced by warfarin [1 case], no antiplatelet or single antiplatelet clinically indicated and clopidogrel chosen [4 cases], patient choice without evidence of recurrent hypersensitivity [1 case], and death due to cardiogenic shock following STEMI [1 case]). Conclusion: A rapid aspirin desensitization protocol is safe and effective across a broad spectrum of hypersensitivity reactions and clinical presentations.